Cogito Ergo Sum: Understanding the Professional Skepticism of Government Internal Auditors - Fatkhmol Risepdo; Erina Sudaryati (Universitas Hayam Wuruk Perbanas, 2025)
Descartes' philosophy, famous for the phrase